1986
DOI: 10.1017/s0043174500068338
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Control of Waterhyacinth (Eichhornia crassipes) with a Pathogen, Insects, and Herbicides

Abstract: Although the problems with waterhyacinth (Eichhornia crassipes[Mart.] Solms; # EICCR) have diminished in the United States over the last decade, the weed continues to be troublesome and requires constant management on a maintenance basis (29, 30). Chemical herbicides are currently the principal means of control when an immediate solution to a waterhyacinth problem is needed. Preventive maintenance programs also rely on chemicals to keep the weed populations at acceptable levels and to prevent weed migration in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
3

Year Published

1989
1989
2011
2011

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(44 citation statements)
references
References 14 publications
1
40
0
3
Order By: Relevance
“…Freeman and Charudattan (1984) recorded better control of waterhyacinth in Florida when Cercospora rodmanii was used in combination with waterhyacinth insects where the latter were used to cause injury on leaves. Similarly in several studies, it has been observed that the use of pathogen has resulted in more severe damage to the insect damaged plants because of lowered resistance (Conway, 1976;Freeman et al, 1976;Charudattan era/., 1978;Charudattan, 1986). Another important observation made in the present study is that young leaves showed less infection than mature leaves in the field as well as in pits (Figure 1) indicating that young leaves are comparatively more resistant to A. alternata.…”
Section: Resultssupporting
confidence: 82%
“…Freeman and Charudattan (1984) recorded better control of waterhyacinth in Florida when Cercospora rodmanii was used in combination with waterhyacinth insects where the latter were used to cause injury on leaves. Similarly in several studies, it has been observed that the use of pathogen has resulted in more severe damage to the insect damaged plants because of lowered resistance (Conway, 1976;Freeman et al, 1976;Charudattan era/., 1978;Charudattan, 1986). Another important observation made in the present study is that young leaves showed less infection than mature leaves in the field as well as in pits (Figure 1) indicating that young leaves are comparatively more resistant to A. alternata.…”
Section: Resultssupporting
confidence: 82%
“…In the vast territory of China with its vast differences in environmental conditions in various provinces, the practical strategy for integrated management of waterhyacinth should be chosen according to the local conditions including the climate, level of water pollution, and local affordability [9] , such as saving of the perished frond in winter in South-Eastern China, releasing exotic weevils and/or local insects in Southern China, and also using chemical hericides in limited areas, where water is not used for drinking. The combination of chemical or mechanical strategy and biological control may greatly increase the effectiveness of integrated management on waterhyacinth [4] . Besides the use of insects, biological control by using plant pathogens has also studied but so far no pathogen has been developed as a bioherbicide.…”
Section: Discussionmentioning
confidence: 99%
“…Black dots often are visible from the reverse side of the petri dish about 7 days after, but they do not extend into the surface of the culture on the upper side of the Petri dish, where the perithecia with orifice were located (see Figs. [3][4][5]. The size of ascus in perithecia is 9-12.5 µm × 11-23 µm, its base is fasciculate and the head is fan-shaped.…”
Section: Identification Of Isolatesmentioning
confidence: 99%
“…It reproduces sexually by seeds (Agami and Reddy 1990). It is one of the most productive plants on earth and is considered the world's worst aquatic plant (Charudattan 1986). Low oxygen conditions do develop beneath water hyacinth mats formed by the plant and the dense floating mats impede water flow and create good breeding conditions for mosquitoes.…”
Section: Study Area and Samples Descriptionmentioning
confidence: 99%